One second after [compact disc, unabridged] - Forstchen, William R. (Blackstone Audio, 2009)
A post-apocalyptic, dire and frightening all-too-possible future for humankind. When an Electro-Magnetic Pulse weapon sends the United States into chaotic ruin, one man battles to save his family and their small North Carolina town.